1994
DOI: 10.3109/02688699409101191
|View full text |Cite
|
Sign up to set email alerts
|

Transoral plate and screw fixation of the craniovertebral region–a preliminary report

Abstract: A transoral plate and screw fixation of the clivus to the body of the cervical vertebra is described. The procedure was successfully performed in a patient with congenital basilar invagination after odontoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Since Goel et al [10] first reported a case of transoral plate and screw fixation of the clivus to the body of the cervical vertebra, several studies have been published using the clival screw fixation for the craniovertebral region [8,9]. However, the anatomy of the clivus and the geometry of the craniocervical junction present challenges for the placement of instrumentation, and also there are no literature that have document the entry point, trajectory, and optimal length of clival screws; our next logical step was to study the anatomic of clival screw fixation for the craniovertebral region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Goel et al [10] first reported a case of transoral plate and screw fixation of the clivus to the body of the cervical vertebra, several studies have been published using the clival screw fixation for the craniovertebral region [8,9]. However, the anatomy of the clivus and the geometry of the craniocervical junction present challenges for the placement of instrumentation, and also there are no literature that have document the entry point, trajectory, and optimal length of clival screws; our next logical step was to study the anatomic of clival screw fixation for the craniovertebral region.…”
Section: Discussionmentioning
confidence: 99%
“…Rawlins et al [9] used a titanium plate to fix the bone graft into the clivus and the body of the 3rd cervical vertebra, as the anterior reconstruction. Goel et al [10] reported a patient with congenital basilar invagination after odontoidectomy performed with plate and screw fixation of the clivus to the body of the 3rd cervical vertebra. It was considered that direct fixation to the clivus may be a more rigid alternative to previously described techniques [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to Menezes and Van Gilder 17 , when osteoarthritis was present in the atlantoaxial joints, posterior fi xation was often not required. Although some authors mention ventral fi xation [26][27][28] , posterior stabilization is more practical and safer 7,29 . Of 38 patients, 18 underwent a posterior fi xation using an inside-outside technique as proposed by Pait et al 7 and two were already fi xed with the Ransford loop technique 29 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Menezes and Van Gilder 17 , when osteoarthritis was present in the atlantoaxial joints, posterior fi xation was often not required. Although some authors mention ventral fi xation [26][27][28] , posterior stabilization is more practical and safer 7,29 . Of 38 patients, 18 underwent a posterior fi xation using an inside-outside technique as proposed by Pait et al 7 and two were already fi xed with the Ransford loop technique 29 .…”
Section: Discussionmentioning
confidence: 99%